2021
DOI: 10.1186/s12903-021-01789-5
|View full text |Cite
|
Sign up to set email alerts
|

Tooth alignment and pain experience with A-NiTi versus Cu-NiTi: a randomized clinical trial

Abstract: Background Nickel-titanium (NiTi) archwires are routinely used for initial leveling and alignment of teeth in orthodontic treatment. This study aimed to clinically compare the level of pain and tooth alignment in orthodontic treatment with A-NiTi versus Cu-NiTi archwires. Methods In this parallel randomized clinical trial, 88 orthodontic patients (12–25 years) with an irregularity index > 2 mm in the anterior site of the lower dental arch who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…analyzed the influence of orthodontic archwire material (NiTi versus Cu-NiTi) on pain in orthodontic patients. This author did not report any statistically significant differences in pain levels or duration between the two groups ( 10 ). In the case of our study, we only observed significant differences ( p < 0.05) when comparing NiTi and Cu-NiTi at the beginning of treatment (T01).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…analyzed the influence of orthodontic archwire material (NiTi versus Cu-NiTi) on pain in orthodontic patients. This author did not report any statistically significant differences in pain levels or duration between the two groups ( 10 ). In the case of our study, we only observed significant differences ( p < 0.05) when comparing NiTi and Cu-NiTi at the beginning of treatment (T01).…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, new material compositions have been developed for use in orthodontic archwires, including copper–nickel–titanium (Cu-NiTi) wires. Various in vitro studies have been conducted to evaluate the performance of these new Cu-NiTi archwires ( 9 ); however, very few clinical studies have been published that address the possible influence of the orthodontic archwire material on pain levels ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study add further scope to studies comparing different aligning archwires. In previous studies, SENT and Copper-NiTi were found to be equally effective for the alignment of lower anterior teeth, 11 HANT and SENT had similar performance in the alignment phase, 12 and 0.014-in SENT and 0.016-in HANT wires had no clinical difference in the amount of tooth alignment or perception of pain. 18 In contrast, a different study indicated that HANT wires were more effective than SENT wires in alleviating crowding.…”
Section: Alignment Effectivenessmentioning
confidence: 79%
“…9 Many clinical trials have studied archwire effectiveness. [10][11][12][13][14] Results have shown inconsistent findings in alignment effectiveness and controversial outcomes in pain perception. Root resorption did not differ significantly among groups; however, one study suggested monitoring with superelastic nickel-titanium (SENT) wires.…”
Section: Introductionmentioning
confidence: 99%
“…Displacement of contact point as described in the index was measured with the help of a digital caliper with a sharpened fine edge to the nearest 0.01 mm (Standard Digital Caliper Series: EC16) on the study models. 19 , 29 , 30 Alignment was considered complete when LII was near zero and 0.019×0.025-in stainless-steel working archwire was passive in the bracket slots (T5).…”
Section: Methodsmentioning
confidence: 99%